Turkish University Students' Self-Perceptions of Aging: An Analysis Over Socio-Economic Dimensions - Aynur Yumurtaci; Bilal Bagis (Global Labor Organization (GLO), 2019)
University students represent nearly more than half of the youth population (age group of 15-24) in Turkey. Meanwhile, the latest demographic data shows that they will constitute a majority of the elder generation in the context of the recent rapid aging trend in the near future. That said, and although the number of studies related to the students' perceptions of old ages are increasing in recent years, there is still room to extend our understanding of the influence of demographics, social and economic patterns on students' self perceptions of old age. To investigate the Turkish students' views towards their own 65+ ages, a questionary is applied to 450 students from two different universities located in different regions in Turkey. Survey analysis shows that, almost 85 percent of “engineering” and “economics and administrative science” faculty students describe health and elderly care as the two major concerns in their old ages. On the contrary, answers of the two faculties differentiated clearly in terms of happiness, ability to save more and living with someone else in their old ages. Also, students accept retirement period as a reflection of aging and most of the students claim they had never thought about the aging process before. Yet, female and male students describe the meaning of retirement as the most comfortable period and a period that makes no sense, respectively.
Keywords: J0; J1; I3; Z19; 330; University Students; Turkey; Aging; Perceptions